1984
DOI: 10.1007/bf00001664
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the biology of the euryhaline Asian cichlid, Etroplus suratensis

Abstract: SynopsisAspects of the biology of the euryhaline Asian cichlid Etroplus suratensis in a coastal lagoon of Sri Lanka were studied for a period of 15 months. Comparisons are made from the catches from the fishery of manmade, inland freshwater reservoirs. Changes in the stock structure in the sublittoral region of the lagoon indicate that recruitment takes place twice a year, during the high rainfall/low salinity periods. The feeding habits of E. suratensis were different in the two habitats. In the lagoon it fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Fish are incapable of digesting plant cellwalls and intact cells of higher plants (Fish, 1955;Stickney & Shumway, 1974). Also the ratio of the intestinal length to body length of E. suratensis ranges from 1.6 : 1.0 to 3.7 : 1-0 (De Silva et al, 1983), which is much less than that of a typical herbivorous species (Fange & Grove, 1979) and as such may be a factor responsible for relatively lower efficiency in protein digestion. The lower protein digestibility seen in E. suratensis may also be partially due to the incomplete rupture of the cells of a proportion of the feed thus preventing their digestion.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Fish are incapable of digesting plant cellwalls and intact cells of higher plants (Fish, 1955;Stickney & Shumway, 1974). Also the ratio of the intestinal length to body length of E. suratensis ranges from 1.6 : 1.0 to 3.7 : 1-0 (De Silva et al, 1983), which is much less than that of a typical herbivorous species (Fange & Grove, 1979) and as such may be a factor responsible for relatively lower efficiency in protein digestion. The lower protein digestibility seen in E. suratensis may also be partially due to the incomplete rupture of the cells of a proportion of the feed thus preventing their digestion.…”
Section: Discussionmentioning
confidence: 97%
“…This species has been successfully transplanted into man-made reservoirs in Sri Lanka and is an important constituent of the inland fishery (Fernando & Indrasena, 1969;De Silva & Fernando, 1980) as well as in coastal lagoons (Ward & Wyman, 1977). In the inland reservoirs it is known to feed on macrophytes (De Silva et al, 1983). It is also recognized as a potential candidate for culture in Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%
“…Except the recent research on captive breeding and seed production of pearlspot in raceway tanks (Padmakumar et al 2009b), no research has been conducted to evaluate different stocking densities for fry rearing in controlled conditions, such as pond or tanks. As this fish is a bottomdwelling species (de Silva, Maitipe & Cumaranatunge 1984), role of soil base in indoor rearing system also remains unknown. Lack of information on pearlspot seed rearing method especially in indoor tank necessitates for carrying out a well-designed trial.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies it has been demonstrated that relative gut length indicated that morphological features are correlated to feeding habits (Kapoor et al, 1976;De Silva et al, 1980;Karachle and Stergiou, 2010), and also that in a species it could vary depending on the habitat and the type of food ingested (De Silva et al, 1984). Noncarnivores in general need more time to digest food types like plants, detrital material, fragments, or small crustaceans in the extended intestine for abundant nutrient breakdown and absorption.…”
Section: Discussionmentioning
confidence: 99%